2010
DOI: 10.1097/mao.0b013e3181d27740
|View full text |Cite
|
Sign up to set email alerts
|

A Superior Semicircular Canal Dehiscence Syndrome Multicenter Study

Abstract: Patients with larger superior canal dehiscences show significantly more vestibulocochlear symptoms/signs, lower VEMP thresholds, and objective vestibular findings compared with smaller ones. Smaller dehiscences mainly present with either cochlear or vestibular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 24 publications
2
53
3
2
Order By: Relevance
“…Pfammatter et al [2010] divided 27 patients based on their symptoms and signs and evaluated the association between the symptoms/signs and the size of the SCD. They reported that the patient group with a larger-size SCD ( ≥ 2.5 mm) presented predominantly with cochleovestibular symptoms and/or signs, lower VEMP thresholds and objective vestibular findings.…”
Section: Discussionmentioning
confidence: 99%
“…Pfammatter et al [2010] divided 27 patients based on their symptoms and signs and evaluated the association between the symptoms/signs and the size of the SCD. They reported that the patient group with a larger-size SCD ( ≥ 2.5 mm) presented predominantly with cochleovestibular symptoms and/or signs, lower VEMP thresholds and objective vestibular findings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently demonstrated that dehiscence of Ն2.5 mm on CT is associated with significantly more vestibulocochlear symptoms than smaller dehiscences, 18 perhaps because a relatively high number of small dehiscences seen on CT are probably not correlated with a real anatomic dehiscence. 17 When SC dehiscence was seen, the measure of the dehiscence obtained with FIESTA was, on average, Ͼ50% higher than the CT value, congruent with the assumption that FIESTA is less sensitive than CT in depicting very thin bone coverage; because of this difference, the 2.5-mm threshold used with CT cannot be transposed to FIESTA.…”
Section: Discussionmentioning
confidence: 99%
“…La primera encontrada es la presencia de un defecto óseo completo (dehiscencia) localizado en el arco del canal semicircular superior, que hemos encontrado en un único caso. La dehiscencia del canal semicircular superior es un síndrome hoy día bien establecido como una forma de vestibulopatía periférica que puede cursar con alteraciones vestibulares y/o auditivas en unos casos, y en otros ser completamente asintomático (Hillman et al, 2006), habiendo indicios clínicos que relacionan la presencia de sintomatología vestibular y auditiva con el tamaño de la dehiscencia (Pfammatter et al, 2010).…”
Section: Discussionunclassified